The Influence of Price and Presentation Techniques on the Success of Bidding CV Reel Seven Organizer Palembang - Lubis, Aditya Francisco; Saragih, Agus Mariani (CV. Civiliza Publishing, 2025)
The increasingly intense competition in the event industry requires every event organizer (EO) company to improve the quality of their services and marketing strategies in order to win bids (tenders) for organizing events from both government and corporate clients. The success of bidding is one of the key factors that determine an EO company's success in becoming the selected event organizer, which is essential for the company's sustainability and growth. This study aims to analyze the influence of pricing and presentation techniques on bidding success at CV Reel Seven Organizer in Palembang. A quantitative approach was used, employing a survey method involving 75 respondents who are clients of CV Reel Seven Organizer. The independent variables in this study are price and presentation technique, while the dependent variable is bidding success. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The validity and reliability tests showed that all research instruments were valid and reliable. The t-test results indicated that both price and presentation technique have a significant partial effect on bidding success. Meanwhile, the F-test indicated that both independent variables simultaneously have a significant effect on bidding success. The coefficient of determination (R²) showed that price and presentation technique contribute 62.8% to the variation in bidding success. These findings highlight the importance of setting competitive prices and using effective presentation techniques to attract and gain the trust of clients. Therefore, companies need to pay close attention to pricing strategies and improve presentation skills in every bidding process.